1996
DOI: 10.1115/1.2788865
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Study of the Applicability of Rigid-Body Collision Theory

Abstract: This article deals with the collision of steel bars with external surfaces. The central issue of the article is the investigation of the fundamental concepts that are used to solve collision problems by using rigid body theory. We particularly focus on low velocity impacts of relatively rigid steel bars to test the applicability of these concepts.An experimental analysis was conducted to study the rebound velocities of freely dropped bars on a large external surface. A high speed video system was used to captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 12 publications
5
99
0
4
Order By: Relevance
“…They explicitly verified that the assumption of Coulomb's law of dry friction, which is essential to Keller's theory, is satisfied for impact velocities of the order of a few meters per s and that the coefficient of restitution does not depend much on the particle size or the impact velocity. It was found in [18] that may depend strongly on the orientation of the particle, but this was attributed to the excitation of longitudinal vibrations of the particle. In the case of a metal particle-belt collision, the energy is absorbed by the belt rather than by the particle and the energy is absorbed locally, near the impact, independently of the shape and orientation of the particle.…”
Section: Mechanical Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They explicitly verified that the assumption of Coulomb's law of dry friction, which is essential to Keller's theory, is satisfied for impact velocities of the order of a few meters per s and that the coefficient of restitution does not depend much on the particle size or the impact velocity. It was found in [18] that may depend strongly on the orientation of the particle, but this was attributed to the excitation of longitudinal vibrations of the particle. In the case of a metal particle-belt collision, the energy is absorbed by the belt rather than by the particle and the energy is absorbed locally, near the impact, independently of the shape and orientation of the particle.…”
Section: Mechanical Interactionsmentioning
confidence: 99%
“…In our study, was taken as a constant, independent of the size, shape, impact, velocity, or orientation of the particle. Such a simplification can be defended on the basis of a study by Stoianovici et al [18] who showed that the rigid body theory performs remarkably well as long as little of the energy is absorbed by the system as longitudinal vibrations of the particle. They explicitly verified that the assumption of Coulomb's law of dry friction, which is essential to Keller's theory, is satisfied for impact velocities of the order of a few meters per s and that the coefficient of restitution does not depend much on the particle size or the impact velocity.…”
Section: Mechanical Interactionsmentioning
confidence: 99%
“…More fundamentally, the coefficient of restitution is physically meaningful only for particles, and it has been difficult to define a suitable quantity for rigid bodies [MC95]. Even for something as simple as a metal rod, the measured coefficient of restitution can vary over most of the feasible range [SH96]. The other alternative is to introduce virtual springs and dampers at the contact points (e.g., [GPS94]), to remove the contact state sensitivity.…”
Section: Figure 1: a Romance Of Two Computer Graphics Classics (A) Tmentioning
confidence: 99%
“…However, many different models were developed to describe the restitution coefficient of viscoelastic (Schafer et al [79], Stronge [88], Stoianovici and Harmuzlu [87]), viscoelastic-adhesive (Thornton and Ning), viscoelastic (Brilliantov [11]), elastic-perfectly plastic (Thornton [93], Wu et al [109]), elastic-perfectly plastic adhesive (Thornton and Ning [94]), elastic-perfectly plastic with hardening (Mangwandi et al [64]), elastic-plastic (Johnson [38]), elastic-viscoplastic (Adams et al [3]), plastic and viscoplastic (Walton and Braun [106]), elastic-adhesive (Thornton and Ning [94]) contacts. A review of these models is given in Table 1.…”
Section: Significant Factors Affecting the Restitution Coefficientmentioning
confidence: 99%